ADOPTION OF E-COMMERCE BY SMES: INTERNAL READINESS AND GOVERNMENT SUPPORT - Fandhitya Silalahi , Sahat Aditua; Fachrurazi, (International Journal of Psychosocial Rehabilitation, 2020)
SMEs, as the majority form of business in Indonesia, must be able to adopt e-commerce technology in order to serve their customers better. The government is also obliged to support the use of e-commerce for SMEs since this business unit is the primary driver of the local economy. Therefore, this paper aims to study the level of SME readiness to implement e-commerce, especially in financial, human resources, and supporting infrastructure aspects. This paper also investigates the level of satisfaction toward government support. The research is a quantitative study using a Likert-Scale questionnaire as an instrument for collecting data. The respondents were 215 SMEs in Bogor Regency who had obtained assistance from the government. The results show that SMEs have demonstrated adequate readiness in the information technology infrastructure aspects, as indicated by high scores on the ease of internet access. SMEs have not shown readiness in financial aspects indicated by a lack of capital and investment plan. The respondents also have not shown readiness in the aspect of human resources indicated by a low level of awareness of the benefits of e-commerce. Meanwhile, SMEs have shown a high level of satisfaction toward e-commerce support from the government, especially in terms of providing training. However, respondents have a low level of satisfaction in the funding program and the sustainability of government support.